Pengaruh Layanan ATM dan Mobile Banking terhadap Loyalitas Nasabah Bank Sulselbar Cabang Sinjai - Nurul Fadhilah; Damirah (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2020)
This study aims to determine the effect partially and simultaneously service variables Reliability (Reliability), Responsiveness (Responsiveness), Assurance (Assurance), Empathy (Empathy) and Tangible (Physical Evidence) on customer loyalty of Bank Sulselbar Sinjai Branch. This research is a type of quantitative research with descriptive methods and a survey on the company. The population in this study were customers of Bank Sulselbar Sinjai Branch who use ATM and Mobile Banking products, with determining the type of sample using the Slovin formula. The data collection used in this research is a questionnaire / questionnaire. The method used to test the hypothesis is to use correlation analysis between variables, statistical analysis, multiple regression analysis test, and statistical test. The results showed: based on the partial test results or T test that the variable Responsiveness (Responsiveness) (X2) with a significant value of 0.001 <0.05 and the value of tcount (3,424)> t table (1.994) and the variable Reliability (Reliability) significant value 0.042 <0.05 and tcount (2.074)> t table (1.994) has a significant effect on customer loyalty (Y). Meanwhile, the Assurance variable (X3) with a significant value of 0.955> 0.05 and the value of tcount (0.065) <ttable (1.994), Empathy (Empathy) (X4) with a significant value of 0.065> 0.05 and tcount (- 1.873) <t table (1.994) and Tangible (Direct Evidence) (X5) with a significant value of 0.069> 0.05 and the value of tcount (1.847) <t table (1.994) had no significant effect. Based on the results of simultaneous testing or the F test, it shows that technology-based product service variables affect customer loyalty (Y) together